Protective effect exerted by soil phosphorus on soybean subjected to arsenic and fluoride - Bustingorri, Carolina (2017)
Objetive: Arsenic (As) and fluoride (F) are found in groundwater and soils around the world, causing different problems to crops. Because these elements compete against phosphorus (P) in soils and plants, their relationship is complex. The aim of this work was to study the oxidative stress of soybean plants subjected to different concentrations of As and F, and the effect of P. Methods: The following 10 treatments were carried out in each of two soils with different P content: three As levels (low 10 mg As kg-1, medium 50 mg As kg−1 and high 100 mg As kg−1), three F levels (low 160 mg F kg−1, medium 250 mg F kg−1 and high 500 mg F kg−1) and three As + F levels (same concentrations), and the control treatment (soil with the background As and F concentrations) Lipid peroxidation, chlorophyll, gluthatione contents and antioxidant enzymes activities were determination. Results: Increased lipid peroxidation and alterations in glutathione content, catalase, superoxide dismutase and peroxidase activities as well as in chlorophyll content revealed that As causes higher oxidative stress in plants grown in soils with low P content. Conclusion: Stress parameters in F treatments were less affected. Plants grown in soils enriched with P revealed a decrease in the toxic effects caused by As and F.